THE EFFECT OF FARTLEX AND EXTENSIVE INTERVAL TRAINING METHOD TOWARD THE FOOTBALL REFEREES SPEED ENDURANCE IN PADANG (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Many referees fail in following the physical capability test. The failure is caused by the low rate of physical fitness of the referees themselves. One of the factors that cause this condition is the physical training method. This research was aimed at knowing the effectiveness of the interval ekstensif training method and fartlek training method on the referees speed endurance. This research was a quantitative study and employed a quasi experimental design. The population of this research was 75 people = 37 had C3 licence, 13 people had C2 licence, 24 people had C1 licence and 1 person had FIFA licence. The sample was taken based on purposive sampling technique in which 20 referees were chosen. The technique of data collection was test and the instrument used was the physical capabilities test 20x150 meters. Finally the data was analyzed by using t test. The data analysis indicated that: The interval training method could improve speed endurance capabilities 20x150 meters with 21,75 > 2,26 (Mean pretest 30,86 and posttest 29,12 second). The fartlek training method could improve speed endurance capabilities 20x150 meters with 7,89 > 2,26 (Mean pretest 30,88 and postest 30,17 second). There was a significant difference between the interval ekstensif training method and fartlek training method on speed endurance capabilities 20x150 metres withÂ  3,28 > 2,101. Based on the data above, it could be concluded that both training methods could improve the physical abilities of 20x150 meters; the interval ekstensive methods contributed a better influence than the fartlek methods. Furthermore it is suggested that all football referees use the interval ekstensive method and fartlek to improve the speed endurance capabilities of 20x150 meters.